KONSTRUKSI IDEOLOGI MUHAMMADIYAH DALAM TAFSIR AL-AZHAR: SEBUAH ANALISIS WACANA KRITIS - Salsadilah, Nijma Auliah; Indal Abror (EL-MAQRA', 2025)
This research analyzes how Muhammadiyah ideology influences Buya Hamka's interpretation in his Tafsir Al-Azhar through Fairclough's Critical Discourse Analysis (CDA). Using library research methodology with a qualitative approach, this study examines three selected Quranic verses: QS. Ali 'Imran :104 (structured da'wah), QS. Al-Baqarah :170 (rationalism and anti-taqlid), and QS. Al-Ma'un :1-7 (concrete social action). The findings reveal that Hamka consistently employs lexical choices and discourse strategies that reflect three dimensions of Muhammadiyah ideology: (1) structured organization, (2) rationalism, and (3) concrete social action. At the textual level, word choices such as "systematic," "organized," and "good management" demonstrate that da'wah is a collective project requiring organizational structure. At the discourse level, Hamka employs rhetorical strategies to provide Quranic legitimacy for Muhammadiyah's da'wah program. At the socio-cultural level, the tafsir functions as a medium for socializing organizational values to its readers. The three dimensions are integrated into a consistent narrative pattern: rational thinking structured organization concrete social action. This research contributes to understanding the role of tafsir as an arena where religious meaning is contested and reconstructed according to the contextual needs of modern Islamic movements. The research implications are relevant to tafsir studies, inter-Islamic tradition dialogue, and religious education in Indonesia.